Effect of Diffusing Elements in a Reverberation Room on the Results of Airborne Sound Insulation Laboratory Measurements - MLECZKO, Dominik; WSZOŁEK, Tadeusz (Archives of Acoustics, 2019)
The main problem in the measurement of airborne sound insulation is the measurement of the sound power radiated by the barrier, in practice performed by measuring the sound pressure level and the acoustic absorption in the receiving room. Large variations of the sound pressure level in a reverberation room indicate the presence of dominating strong standing waves, so that it becomes necessary to install diffusing elements. In ISO 10140, the limits have been defined in which the reverberation time at frequencies at and above 100 Hz should be included. Sometimes, however, in the case of rooms with a large volume, obtaining the required parameters is difficult and sometimes even impossible. It should then be checked whether the measured sound insulation depends on the reverberation time.The paper presents the results of sound insulation measurements at various reverberation time lengths in subsequent stages of diffusing elements installation in the receiving room. An analysis of diffusing materials amount and arrangement influence on the uniformity of the sound pressure level distribution and reverberation time in the room as well as the value of the measured sound insulation was carried out. Uncertainty of sound insulation measurement with partial uncertainties was adopted as a criterionsupporting the assessment of the obtained results.